NUTRITIONAL STATUS ASSOCIATED WITH MENSTRUATION DISORDERS - Yulfitria, Fauziah; Kusumastuti, Ani; Ichwan, Erika Yulita (Asosiasi Pendidikan Kebidanan Indonesia, 2018)
Menstrual disorders such as delayed menstruation, irregular cycle, menstrual pain, or hypermenorea can bring so much discomfort to women caused by biological abnormalities and psychological factors. However, nutritional status can also play a role in contributing to this disorder. This study aimed to determine the relationship of nutritional status to menstrual disorders in midwifery students. This descriptive analytical study used a cross sectional study design and a correlation study to find the relationship between the independent variables and dependent variables. The samples were all the first grade students of Midwifery Department of Poltekkes Jakarta Kemenkes III by 150 people. Based on the bivariate test, there was a relationship between nutritional status and polimenorea/oligomenorea (0.000), hipermenorea/hipomenorea (0.006) and amhea (0.001). The lecturers of the midwifery program are expected to put more concern on this problem by providing counseling about this issue so that the students can get prepared to face the disorder by having nutritional food in their daily life.